KONTRIBUSI PENDAPATAN BURUH USAHA PABRIK TAHU MAS GENDON TERHADAP PENDAPATAN KELUARGA DI KELURAHAN KAROMBASAN UTARA KECAMATAN WANEA KOTA MANADO - Palit, Merry Claudia; Tangkere, Ellen; Mandei, Juliana R. (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine the contribution of the income of Mas Gendon's tofu factory workers to family income. This research was conducted in North Karombasan Village, North District, Manado City. The data used in this research are primary data and secondary data. Primary data were obtained from direct interviews with owners and workers of the tofu factory Mas Gendon by distributing questionnaires, secondary data obtained through monograph data and the internet. The Â number of respondents is 5 people. The method of taking respondents using the census method is to make the entire population. The variables measured were the characteristics of the respondents, the income of the workers' family members, the reasons for working, and the time spent by the workers. The data analysis method used is family income and contribution. Based on the results of the research, the contribution of the income of Mas Gendon's tofu factory workers to family income in the North Karombasan Village, Wanea District, Manado City, workers get a wage of 2,000,000/month, and get housing and eating facilities. The time spent by workers in domestic activities is 1.8 hours, productive activities are 16 hours, and other activities are 6.2 hours. Income from workers has a contribution of (76.92%) which is categorized as very large because the value is >50% of the contribution criteria, income from other family members is (23.08%) which is categorized as being in the contribution category.